2013
DOI: 10.1016/j.scr.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The CSF-1 receptor fashions the intestinal stem cell niche

Abstract: Gastrointestinal (GI) homeostasis requires the action of multiple pathways. There is some controversy regarding whether small intestine (SI) Paneth cells (PCs) play a central role in orchestrating crypt architecture and their relationship with Lgr5+ve stem cells. Nevertheless, we previously showed that germline CSF-1 receptor (Csf1r) knock out (KO) or Csf1 mutation is associated with an absence of mature PC, reduced crypt proliferation and lowered stem cell gene, Lgr5 expression. Here we show the additional lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 28 publications
(64 reference statements)
1
31
4
Order By: Relevance
“…Csf1 promoter-driven transgenic expression of the cell surface isoform of CSF-1 in Csf1 op/op mice rescues the macro phage and PC deficiencies, as well as stem cell activity suggesting that CSF-1 regulates intestinal development, in a juxtacrine or paracrine manner (Huynh et al, 2009). In addition, intestine-specific deletion of Csf1r reproduced the Csf1r −/− phenotype, formally proving that CSF-1R cell autonomously supports PC development (Akcora et al, 2013). These studies also showed that the CSF-1R is essential for de novo generation of PC, but not for their survival and demonstrated the critical role of CSF-1R regulation of PC in the maintenance of intestinal stem cells.…”
Section: Direct Regulation Of Nonhematopoietic Cells By the Csf-1rmentioning
confidence: 75%
See 2 more Smart Citations
“…Csf1 promoter-driven transgenic expression of the cell surface isoform of CSF-1 in Csf1 op/op mice rescues the macro phage and PC deficiencies, as well as stem cell activity suggesting that CSF-1 regulates intestinal development, in a juxtacrine or paracrine manner (Huynh et al, 2009). In addition, intestine-specific deletion of Csf1r reproduced the Csf1r −/− phenotype, formally proving that CSF-1R cell autonomously supports PC development (Akcora et al, 2013). These studies also showed that the CSF-1R is essential for de novo generation of PC, but not for their survival and demonstrated the critical role of CSF-1R regulation of PC in the maintenance of intestinal stem cells.…”
Section: Direct Regulation Of Nonhematopoietic Cells By the Csf-1rmentioning
confidence: 75%
“…They have additional roles as regulators of detoxification, digestion, and in the regulation of stem cells as components of the stem cell niche (Clevers & Bevins, 2013; Porter, Bevins, Ghosh, & Ganz, 2002; Wehkamp & Stange, 2006). In both Csf1 op/op and Csf1r −/− mice, there is abnormal organization of the small intestine, with marked reductions of epithelial cells, including PC and intestinal stem cells, and of interstitial macrophages of the villi (Akcora et al, 2013; Cecchini et al, 1994; Huynh et al, 2009). PCs express the CSF-1R and reside in close proximity to CSF-1-expressing epithelial cells within the crypt (Huynh et al, 2009).…”
Section: Direct Regulation Of Nonhematopoietic Cells By the Csf-1rmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated intestinal stem cell niche functions for Paneth or colonic goblet cells (Durand et al, 2012;Farin et al, 2012;Rothenberg et al, 2012;Sato et al, 2011). Similarly, enteroids deficient for Csf1r(-/-), which have a defect in Paneth cell production, showed defective enteroid formation (Akcora et al, 2013).…”
Section: Commentary Background Informationmentioning
confidence: 99%
“…These epithelial organoid culture systems have been used to test the ability of isolated single cells to function as stem cells in vitro, thus testing the "stemness" of isolated cells 5,6,[10][11][12][13][14][15] . Other investigators have used both enteroids and colonoids to study the function of individual epithelial cells [16][17][18][19][20][21] . Thus, enteroid and colonoid cultures can be used to evaluate both stem and non-stem cell functions and give new insight into fundamental cellular interactions within the intestines.…”
Section: Introductionmentioning
confidence: 99%